2012
DOI: 10.1007/s00467-012-2299-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel INF2 mutation p. L77P in a family with glomerulopathy and Charcot-Marie-Tooth neuropathy

Abstract: Our study confirms the link between INF2 mutations and CMT-associated glomerulopathy and widens the spectrum of pathogenic mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Nerve conduction studies showed demyelinating neuropathy with upper limb motor nerve conduction velocities of 13.4 to 32.7 m/s. 8,9 The p.Gly114Asp mutant is predicted to cause serious sterical hindrance of the Met65 and Val108 residues; the latter amino acid is mutated in a reported patient. Brain abnormalities under the form of enlarged lateral ventricles were found in patient PN-2138.1 and CMT-170.02 who also displayed marked psychomotor developmental delay with mental retardation.…”
Section: Resultsmentioning
confidence: 98%
“…Nerve conduction studies showed demyelinating neuropathy with upper limb motor nerve conduction velocities of 13.4 to 32.7 m/s. 8,9 The p.Gly114Asp mutant is predicted to cause serious sterical hindrance of the Met65 and Val108 residues; the latter amino acid is mutated in a reported patient. Brain abnormalities under the form of enlarged lateral ventricles were found in patient PN-2138.1 and CMT-170.02 who also displayed marked psychomotor developmental delay with mental retardation.…”
Section: Resultsmentioning
confidence: 98%
“…INF2 mutations were first reported in patients with CMT and FSGS in 2011 (Boyer et al, ) . Several studies have indicated that INF2 mutations are a main cause of dual pathology in patients of different ethnic groups (Mademan et al, ; Rodriguez et al, ; Toyota et al, ) . Clinically, patients with INF2 mutations show sensorimotor polyneuropathy and FSGS as well as sensorineural hearing loss and demyelinating brain lesions.…”
Section: Discussionmentioning
confidence: 99%
“…FSGS is a cause of nephrotic syndrome and the most common primary glomerular disorder that causes end‐stage renal disease; however, the reason for the association is unclear, as FSGS is associated with a variety of causes such as viral infection, genetic defects, and toxin exposure (D'Agati et al, ) . Recent studies have identified mutations in the inverted formin‐2 ( INF2 ) gene as the major cause of autosomal dominant intermediate Charcot‐Marie‐Tooth disease (DI‐CMT) and FSGS (Boyer et al, ; Mademan et al, ; Rodriguez et al, ) . In this study, we identified a causative mutation in a Korean family with DI‐CMT and FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…Disease-associated amino acid substitutions and insertions of human INF2 are shown below the alignment, while deletions ((x2206)) are shown above the alignment. Mutations are color coded to indicate association with FSGS ( yellow ), CMT-FSGS ( red ), both FSGS and CMT-FSGS ( cyan ), or both FSGS and TMA ( green ) [Brown et al, 2010; Boyer et al, 2011a; Boyer et al, 2011b; Lee et al, 2011; Gbadegesin et al, 2012; Barua et al, 2013; Lipska et al, 2013; Mademan et al, 2013; Rodriguez et al, 2013; Sanchez-Ares et al, 2013; Toyota et al, 2013; Caridi et al, 2014; Laurin et al, 2014; Park et al, 2014; Quaglia et al, 2014; Roos et al, 2015; Xie et al, 2015; Bullich et al, 2015; Jin et al, 2015; Münch et al, 2016; Rood et al, 2016; Challis et al, 2017]. Numbers indicate amino acid positions.…”
Section: Figurementioning
confidence: 99%